Associação da espessura do músculo adutor do polegar e da força de preensão palmar com o estado nutricional em pacientes com câncer - Valente, Katarina Papera (2018)
INTRODUCTION: Malnutrition in cancer is a frequent problem and significantly interferes with the course of the disease, response to treatment and patient survival. The evaluation of the nutritional status at hospital admission is fundamental to verify the present alterations and to individualize the nutritional-clinical intervention. Among the nutritional assessment methods are Tickness of the adductor pollicis muscle (TAPM), Hangrip Strenght (HGS) and Patient-Generated Subjective Global Assessment (PG-SGA). Many studies have found correlation between TAPM and HGS and conventional methods, but not quite researched about this in cancer patients. Thus, the objective of this research was to investigate the association TAPM and HGS and the classical anthropometry and with the PG-SGA. METHODS: The population was composed of patients with cancer candidates for surgery. After applying the exclusion criteria, the final sample was 80 patients. The variables weight, height, Body mass index (BMI), arm circumference (AC), tricipital skin fold (TSF), arm muscle area (AMA), calf circumference (CC), mid-arm muscle circumference (MAMC), TAPM, HGS and PG-SGA were included. The normality of the variables was tested using the Kolmogorov-Smirnov test. Student's t-tests were used to compare the means and Pearson's correlation was used to evaluate the correlation. Multivariate linear regression was used to detect the influence of selected variables on TAPM and HGS. Data were analyzed in SPSS 21.0 software and the significance level of 5.0% was adopted. RESULTS: There was a predominance of males (56.3%, n=45), elderly (60.0%, n=48), non-white (51.2%, n=41) and tumors located in the gastrointestinal tract (76.2%, n=61). The PG-SGA indicated that (60%, n=48) presented some degree of malnutrition and their score indicated that 70% (n=58) of the patients had 9 or more points. As for TAPM of both hands, more than 40.0% of the patients were classified as well nourished. DHGS was adequate for 60% of the patients, while for NDHGS 50.0% of the patients presented this adequate measure and 50.0% inadequate. In the EMAPD regression model, after adjustment with age and sex, the CB variable remained, explaining 54% of the measure. In the NDTAPM model, TSF remained, accounting for 44% of the measure. For the DHGS, the variables AMA, PG-SGA score and age remained, accounting for 81% of the measure. Regarding NDHGS, only the variable age remained, explaining 77% of the measure. CONCLUSION: The inclusion of TAPM and HGS in the hospital routine is indicated because they have been associated with conventional anthropometry and gold standard, but a cut-off point must be created for this population.